Keragaman Genetik Gen Penyandi Dehydrogenase Sub-unit 3 Mitokondria pada Monyet Hantu (Tarsius sp.) (GENETIC DIVERSITY OF MITOCHONDRIAL DEHYDROGENASE SUB-UNIT 3 GENE ON TARSIUS SP.) - Widayanti, Rini; Handayani, Niken Satuti Nur; Budiarsa, I Made (Jurnal Veteriner; Vol 12 No 1 (2011), 2012)
Tarsius is an endemic species in Indonesia but is is getting threatened. In-situ and ex-situ conservationof this species would yield better results when its genetic information and diversity determined. Theobjective of this ressearch was to study the genetic diversity of ND3 gene of Tarsius sp. Based on sequencingof PCR products using primer ND3F and ND3R resulted in 437 nts base sequence. Results of ND3 fragmentssequencing were put on multiple alignment with other primates from Genbank using of software ClustalW, and then were analyzed using MEGA program version 4.1. A different nucleotide site was found(nucleotide no. 24). The genetic distance based on nucleotide ND3 was calculated using Kimura 2-parametermodel. The genetic distance showed the smallest genetic distance 0%, the biggest 0,03% and average0,01%. The phylogenetic tree using neighbor joining method based on the sequence of nucleotide ND3 genecould not be used to differentiate among T. Dianae (from Central Sulawesi), T. Spectrum (from NorthSulawesi) and T. bancanus (from Lampung, South Sumatera).
Keywords: Tarsius sp., ND3 gene, nucleotide, mt-DNA sequens